Narratives against enslavement from the court rooms of nineteenth-century Brazil : fighting for freedom - Lunow, Clara (New York, NY : Routledge, 2023)
"This book examines the enslavement system in nineteenth-century Brazil, demonstrating the strategies lawyers and plaintiffs used to fight for freedom in court. In nineteenth-century Brazil countless enslaved and freed women and men appealed to court to claim their right to freedom or that of family members. Taken as a whole, these legal suits create a narrative against the institution of slavery. By analyzing 30 individual cases (1810-1881) from various parts of imperial Brazil, this book demonstrates the intricate strategies of argumentation lawyers and plaintiffs conceived to prove the right to freedom of the parties involved and to convince the authorities of it. Enslaved persons did not only protest their enslavement through rebellion, flight, refusal to work, and in everyday life, but produced a statement in the legal sphere against enslavement. This intellectual achievement was realized through the cooperation of lawyers and enslaved plaintiffs alike, functioning through stories of injustices, not through theoretical treatises on the right to liberty. While research on abolition in Brazil has concentrated mainly on public discourse, legislative decrees, and protest actions, this book focusses on the discursive space of courts. It gives both an overview of the enslavement system and intricately analyzes the fight for freedom in court. Narratives of Enslavement is the perfect volume for both students and non-specialist readers and also provides new insights for specialists in this field"--
Keywords: Slavery -- Brazil -- History -- 19th century; Slavery -- Law and legislation -- Brazil -- History -- 19th century; HISTORY / Latin America / South America; HISTORY / Modern / 19th Century; HISTORY / Social History